Incidental Papillary Thyroid Microcarcinoma in an Endemic Goiter Area. (2nd February 2016) - Gürleyik, Emin; Gurleyik, Gunay; Karapolat, Banu; Onsal, Ufuk
Abstract : Clinical and pathological characteristics of incidental papillary thyroid microcancer cases, surgical, medical, and nuclear treatment methods, and patients' outcome were studied during follow-up period of 102 months. We studied 37 patients with incidental papillary thyroid microcancer (I-PTM). The surgical procedure was total thyroidectomy in 29 and hemithyroidectomy in 8 patients. Size, multifocality, and bilateralism of PTM foci, thyroid capsule invasion, and presence of lymphovascular invasion were histopathological parameters. We analysed adjuvant medical and nuclear treatment and patients' outcome during follow-up period of 102 (61–144) months. The prevalence rates of I-PTM were 9.4% in 395 thyroidectomy cases. Histopathological examination reported unifocal disease in 30 and multifocal disease in 7 (18%) patients. Multifocal disease was bilateral in 6 (20.1%) patients. The mean size of the PTM foci was 4.88 mm. The rate of thyroid capsule invasion was 5.4%. All patients received a suppressive dose of LT4 to achieve a low serum TSH level. Adjuvant surgical and nuclear treatment was not performed in our cases. We did not find any negative changes in blood chemistry and ultrasound imaging, and any unfavourable events as locoregional and systemic recurrence. In conclusion, diagnosis of I-PTM is common that multifocality and bilateralism appear as pathologic features. The prognosis is excellent after surgical treatment and TSH suppression. Routine adjuvant nuclear treatment is unnecessary in majority of patients.